De-Oiled Citrus Peels as Feedstock for the Production of Pectin Oligosaccharides and Its Effect on Lactobacillus fermentum, Probiotic Source - Sarkar, Rohan; Nain, Lata; Kundu, Aditi; Dutta, Anirban; Das, Debarup; Sethi, Shruti; Saha, Supradip (Frontiers in Nutrition, 2022)
Citrus (Mousambi, Kinnow and Orange) peel wastes were utilised for the production of pectin after extraction of essential oil. Yield of essential oil and pectin was maximum in orange. Pectin was also characterised by FT-IR and XRD spectroscopy. Degree of esterification (DE) and methoxyl content (MC) was maximum in orange whereas, equivalent weight was maximum in mousambi. Significant increase (61.8%) in Lactobaccilus fermentum population was observed with pectin as compared to sugar. Three source followed Orange > Kinnow > Mousambi trend as a prebiotic source. It was attributed to higher DE as well as higher MC. Enhancement in the bacterial population was in the range of 79.16 to 87.50 %. The present work confirms the potential of pectin as a probiotic source for the enhancement of bacterial population. Thus, it has a large scope for use in food industry targeting circular economy.